Comparative Remission Rates and Tolerability of Drugs for Generalised Anxiety Disorder: A Systematic Review and Network Meta-analysis of Double-Blind Randomized Controlled Trials - Kong, Wenqiang; Deng, Huiyuan; Wan, Jie; Zhou, Yilu; Zhou, Yan; Song, Bihui; Wang, Xiuling (Frontiers in Pharmacology, 2020)
Background: Generalized anxiety disorder (GAD) is one of the most common psychiatric disorders associated with substantial dysfunction and socioeconomic burden. Pharmacotherapy is the first choice for GAD. Remission [Hamilton Anxiety Scale (HAM-A) score ≤7] is regarded as a crucial treatment goal for patients with GAD. There is no up-to-date evidence to compare remission rate and tolerability of all available drugs by using network meta-analysis. Therefore, the goal of our study is to update evidence and determine the best advantageous drugs for GAD in remission rate and tolerability profiles. Method: We performed a systematic review and network meta-analysis of double-blind randomized controlled trials (RCTs). We searched PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Chinese National Knowledge Infrastructure, wanfang data, China Biology Medicine and ClinicalTrials.gov from their inception to March 2020 to identify eligible double-blind, RCTs reporting the outcome of remission in adult patients who received any pharmacological treatment for GAD. Two reviewers independently assessed quality of included studies utilizing the Cochrane Collaboration’s risk of bias tool as described in Cochrane Collaboration Handbook and extracted data from all manuscripts. Our outcomes were remission rate (proportion of participants with a final score of seven or less on HAM-A) and tolerability (treatments discontinuations due to adverse events). We calculated summary odds ratios (ORs) and 95% confidence intervals (CIs) of each outcome via pairwise and network meta-analysis with random effects. Results: Overall, 30 studies were included, comprising 32 double-blind RCTs, involving 13,338 participants diagnosed as GAD by DSM-IV criteria. Twenty-eight trials were rated as moderate risk of bias, four trials as low. For remission rate, agomelatine (OR 2.70, 95% CI 1.74–4.19), duloxetine (OR 1.88, 95% CI 1.47–2.40), escitalopram (OR 2.03, 95% CI 1.48–2.78), paroxetine (OR 1.74, 95% CI 1.25–2.42), quetiapine (OR 1.88, 95% CI 1.39–2.55), and venlafaxine (OR 2.28, 95% CI 1.69–3.07) were superior to placebo. For tolerability, sertraline, agomelatine, vortioxetine, and pregabalin were found to be comparable to placebo. However, the others were worse than placebo in terms of tolerability, with ORs ranging between 1.86 (95% CI 1.25–2.75) for tiagabine and 5.98 (95% CI 2.41–14.87) for lorazepam. In head-to-head comparisons, agomelatine, duloxetine, escitalopram, quetiapine, and venlafaxine were more efficacious than tiagabine in terms of remission rate, ORs from 1.66 (95% CI 1.04–2.65) for duloxetine to 2.38 (95% CI 1.32–4.31) for agomelatine. We also found that agomelatine (OR 2.08, 95% CI 1.15–3.75) and venlafaxine (OR 1.76, 95% CI 1.08–2.86) were superior to vortioxetine. Lorazepam and quetiapine were poorly tolerated when compared with other drugs. Conclusions: Of these interventions, only agomelatine manifested better remission with relatively good tolerability but these results were limited by small sample sizes. Duloxetine, escitalopram, venlafaxine, paroxetine, and quetiapine showed better remission but were poorly tolerated.